The Production of Electricity as an Index of the Physical Volume of Business - Persons, Warren M.; Matthews, Ada M. (The Review of Economics and Statistics, 1928)
which is free from the influence of prices. Bank debits, which afford the most general index of business activity, measure the dollar volume of transactions made through checks, and hence reflect the prices of goods, services (i.e., wages in general), and securities, as well as the volume of transactions; whereas most series expressed in physical units, however well they may reflect general movements, actually apply to some particular phase of activity, such as freight shipments or manufacturing.